The factors influencing intention to join gig economy among hospitality and tourism students - Norshamsiah Ishar (2023)
Research articles generally will investigate on the significant factors influencing involvement and intention to join the gig economy among hospitality and tourism students. The gig economy can be seen as the fuel that ignited change in developed economies around the globe. A cultural change in how we defined and desired how we wished to work gave us flexible work. The purpose of this research is to find out the ways, intentions and methods of students how to start join the gig economy after graduation. The purpose of this study will to investigate the relationship between meaningful work, sense of community, alignment of organizational values and intention to join the gig economy among hospitality and tourism students. A self-administered questionnaire will utilize in conjunction with a disproportionate stratified random sample procedure to participants select. This survey will include hospitality and tourism students at Universiti Malaysia Kelantan. The study aims to provide a detail the independent variable and dependent variable for this study based on variables adapted in Job demands-resources theory, Social Exchange Theory and Theory of Planned Behavior.